Evaluation of Curved Canal Transportation Using the Neoniti Rotary System with Reciprocal Motion: A Comparative Study - Mohsen Aminsobhani; Arvin Rezaei Avval; Fatemeh Hamidzadeh (Hindawi Limited, 2021)
The ideal root canal preparation is where the original canal morphology is maintained during the biomechanical preparation. Preparation of curved canals has always been a challenge to clinicians. Better results have been suggested for a single NiTi instrument with reciprocating motion than the conventional continuous rotation method in the preparation of curved root canals. Although the Neoniti rotary system is not suggested to be used with reciprocal motion, running a pilot study, we found that it could be possible. The present study aimed to investigate if shaping curved canals using the Neoniti rotary system with reciprocal motion leads to better results in terms of root canal transportation. One hundred acrylic j-shape canal simulator endoblocks were used in this study. Five preparation sequences were applied: GPS followed by A1#20 (GPS + A1#20), GPS followed by A1#20 and then A1#25 (GPS + A1#20 + A1#25), GPS followed by A1#25 (GPS + A1#25), hand file followed by A1#20 (hand file + A1#20), and GPS followed by A1#20 (with reciprocal motion) (GPS + A1#20(reciprocal)). Pictures were taken from blocks once before and once after preparation from two dimensions. Before-and-after pictures were superimposed in Photoshop software. Measurements were performed in Digimizer. The number of autoreverses and pecking motions was recorded after reviewing the recorded videos. Data were analyzed in SPSS, version 26. A p value of less than 0.05 was considered statistically significant. The group GPS + A1#20 + A1#25 had more transportation compared with the others, at apical, middle, and coronal thirds not only in the frontal view but also in the lateral view. Other groups were not significantly different. The number of peckings and autoreverses was significantly less when A1#25 was used after GPS and A1#20. When A1#20 was used with reciprocal motion, it had less peckings compared with the same file with continuous rotation, and no autoreverses were observed in that group. Using Neoniti files with reciprocal motion might result in less instrument fatigue and favorable results, with respect to canal anatomy preservation. Using A1#20 before A1#25 also will decrease the stress on the instrument during preparation. However, this may lead to significantly more canal transportation.